TANGIBLE ASSETS IN TERMS OF DISCONNECTION BETWEEN ACCOUNTING AND TAXATION - Mariana GURĂU; Maria Zenovia GRIGORE (Challenges of the Knowledge Society)
The purpose of this paper is to make a summary of the accounting and tax provisions of the tangible assets, regarding the current trend of disconnection between tax and accounting. Also, we are going to put together both tax and accounting provisions and we highlight which are the necessary and compulsory tax documents for fixed assets. In taxation, the principle "guilty until proven innocent" is applyng. That means that responsibility to know the Fiscal Code is an obligation "sine qua non" for taxpayers. Thus, there is in low the principle that "no one can excuse invoking ignorance of the law" ("Nemo censetur ignore legem"). Based on these considerations, we found it necessary to make a summary of the fiscal obligations that have economic entities on fixed assets. This synthesis can provide to a company a basis for strong arguments in discussions with tax authorities that can prevent an aggressive approach of them.